อิทธิพลของการคุกคามจากการเหมารวมและการดูตัวแบบเชิงบวกต่อการรับรู้การคุกคามจากการเหมารวมและความเร็วในการตอบสนองต่อสิ่งเร้าของคนที่มีภาวะตาบอดสี - อนุสรณ์ อาศิรเลิศสิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research examined the effects of stereotype threat and being exposure to positive role models among Thai male color-blind individuals. 44 participants were randomly assigned to 2 (threat/no threat) x 2 (role/ no role) conditions. They were instructed to read stereotype threat message (vs. no threat) and watch positive role model video (vs. no role model), attend Stroop Task game to measure their reaction time and rate stereotype perception questionnaire in that order. Two-way ANOVA analysis showed that there were interactions between threats and role model conditions on both perceived stereotype threat and reaction time on the Stroop Task. When participants received both threat massage and positive roles model, participants felt significantly less threatened, as well as, performed better at Stroop Task. However, no main effects were found in both stereotype perception and reaction to stimulus, suggesting the effect of stereotype threat depending on whether participants watched positive role model video.